Socially assistive robots in health and social care: Acceptance and cultural factors. Results from an exploratory international online survey - Papadopoulos, Irena; Wright, Steve; Koulouglioti, Christina; Ali, Sheila; Lazzarino, Runa; Martín-García, Ángel; Oter-Quintana, Cristina; Kouta, Christiana; Rousou, Elena; Papp, Katalin; Krepinska, Radka; Tóthová, Valerie; et al. (My University, 2023)
This study explored the views of an international sample of registered nurses and midwives working in health and social care concerning socially assistive robots (SARs), and the relationship between dimensions of culture and rejection of the idea that SARs had benefits in these settings.
Keywords: artificial intelligence; cultural dimensions; socially assistive robots; technology acceptance